Assessment of balance asymmetry in elite polish greco-roman style wrestlers using the Y-balance test - Kruszewski, A.; Kruszewski, M.; Tabecki, R.; Kruszewski, M.; Kuzmicki S. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2025)
Introduction. A wrestling bout is characterised by a short, intense, intermittent effort lasting 6 minutes in total for the senior group, making the need to play 4-5 matches in 1 day, during a wrestling tournament, an additional element of this effort. The ability to maintain balance is manifested through dynamic stability, plays a key role in the sport of wrestling, where precise motor control is essential for the effective execution of techniques and the avoidance of injury. Asymmetries resulting from imbalances can affect players` performance and their susceptibility to injury. The aim of the study was to evaluate asymmetry in the dynamic stability of Polish national team wrestlers in three directions of movement (forward, posteromedial, posterolateral) using the Y-Balance test.